2017
DOI: 10.1097/aln.0000000000001707
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Obstetric Anesthesiology Practice Guidelines in the Republic of Armenia

Abstract: Background Disparity exists in anesthesia practices between high- and low-to-middle income countries, and awareness has been raised within the global health community to improve the standards of anesthesia care and patient safety. The establishment of international collaborations and appropriate practice guidelines may help address clinical care deficiencies. This report’s aim was to assess the impact of a multiyear collaboration on obstetric anesthesia practices in the Republic of Armenia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The following data items were extracted: study details, HRC region, LRC region, the intervention focus (e.g., RA, pain medicine), intervention type (e.g., medical education, research), intervention recipients (e.g., anesthesiologists, residents, fellows), intervention basis, needs assessment method (e.g., standardized tools, informal assessment), evaluation of intervention, it's aspects (e.g., impact, educational) and evaluative research methodology utilized (e.g., qualitative, quantitative). A total of 1314 articles identified by the search, 134 qualified for full text assessment for eligibility, with 44 studies qualifying in the final review [20 ▪▪ ,21,22 ▪ ,23,24 ▪▪ ,25 ▪▪ ,26,27,28 ▪ ,29–63]. There were few studies published in the last 18 months (probably due to COVID travel restrictions) but four studies focused on RA were published recently.…”
Section: Articles On High/low Resource Anesthesia Collaborations From...mentioning
confidence: 99%
“…The following data items were extracted: study details, HRC region, LRC region, the intervention focus (e.g., RA, pain medicine), intervention type (e.g., medical education, research), intervention recipients (e.g., anesthesiologists, residents, fellows), intervention basis, needs assessment method (e.g., standardized tools, informal assessment), evaluation of intervention, it's aspects (e.g., impact, educational) and evaluative research methodology utilized (e.g., qualitative, quantitative). A total of 1314 articles identified by the search, 134 qualified for full text assessment for eligibility, with 44 studies qualifying in the final review [20 ▪▪ ,21,22 ▪ ,23,24 ▪▪ ,25 ▪▪ ,26,27,28 ▪ ,29–63]. There were few studies published in the last 18 months (probably due to COVID travel restrictions) but four studies focused on RA were published recently.…”
Section: Articles On High/low Resource Anesthesia Collaborations From...mentioning
confidence: 99%
“…Three39–41 out of 31 studies (9.6%) reported all of the discrete strategies from the Yamey (n=13) and Barker et al (n=14) frameworks. From the two frameworks combined, 22 (71%) of the studies reported more than 20 discrete strategies 39–60. However, no study made explicit reference to either the Yamey or the Barker et al frameworks.…”
Section: Resultsmentioning
confidence: 99%